A 14-Year-Old Male Adolescent With a Pruritic Annular Rash. Issue 5 (September 2015) - Hamann, Carsten R.; Zumwalt, Jonathan; Jacob, Sharon E.
<x xml:space="preserve">Abstract</x> ABSTRACT A 14-year-old Caucasian male adolescent presented with a 1-month history of a pruritic, annular, rapidly progressing rash on his trunk, flank, back, neck, and face. He noted no sick contacts. Besides pruritus, the lesions were asymptomatic and nonresponsive to topical corticosteroid therapy. A potassium hydroxide preparation was performed to confirm diagnosis.